2015
DOI: 10.1128/aem.02619-14
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of a GAL4 -Like Transcription Factor Improves Cell Fitness and Product Yield in Glycoengineered Pichia pastoris Strains

Abstract: bWith a completely reengineered and humanized glycosylation pathway, glycoengineered Pichia pastoris has emerged as a promising production host for the manufacture of therapeutic glycoproteins. However, the extensive genetic modifications have also negatively affected the overall fitness levels of the glycoengineered host cells. To make glycoengineered Pichia strains more compatible with a scalable industrial fermentation process, we sought to identify genetic solutions to broadly improve cell robustness durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Previous studies also identified mutations of Gal4-like transcription factors and TUP1 to be associated improved growth of P. pastoris . [ 25 , 27 ]; therefore these regulatory hubs and the cAMP/Pka pathway could represent interesting engineering targets for growth optimization of recombinant P. pastoris host strains, specifically in minimal growth conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also identified mutations of Gal4-like transcription factors and TUP1 to be associated improved growth of P. pastoris . [ 25 , 27 ]; therefore these regulatory hubs and the cAMP/Pka pathway could represent interesting engineering targets for growth optimization of recombinant P. pastoris host strains, specifically in minimal growth conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore OCH1 node removal, although leading to a viable phenotype, has already been previously reported to lead to abnormal growth and stress resistance in yeasts [ 21 , 24 ]. As a consequence, attempts have already been made to improve growth of glyco-engineered yeasts [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The highest expression level obtained by this variant is 1.5‐fold higher relative to wild‐type P GAP in limited glucose conditions. As discussed previously, there are more than 20 Gal4‐ like TFs encoded in the P. pastoris genome and these TFs appear to have distinct regulatory effects on cell physiology (Jiang et al, ; Moser et al, ). Therefore, it is likely that at least one Gal4 ‐like TF is responsible for regulation of P GAP as an activator, yet the details of the mechanism are still unknown.…”
Section: Resultsmentioning
confidence: 97%
“…Therefore it is likely that these Gal4 ‐like TFs are responsible for regulation of other pathways. Indeed, Jiang et al () referred to one of these Gal4 ‐like TFs (PP7435_Chr1‐1522) as Pp Att1 as it shows a significant sequence homology to Sc Gal4. They demonstrated that knocking‐out this TF improved thermal tolerance levels, reduced cell lysis defects, and improved robustness in bioreactor cultivation of a glycoengineered P. pastoris strain.…”
Section: Resultsmentioning
confidence: 99%
“…The co-expression of folding and secretion factors (9-10), the optimization of the properties of foreign nucleotide sequence (codon usage) (11), the insertion of multiple recombinant gene copies (12), engineering of glycosylation (13) and secretory pathways (14) continue as topics to improve the performance of Pichia as cell factory (16).…”
Section: Synthetic Biologymentioning
confidence: 99%